1994
DOI: 10.1002/prot.340200405
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic docking: A proposed enhancement to molecular recognition techniques

Abstract: In the classical procedures for predicting the structure of protein complexes two molecules are brought in contact at multiple relative positions, the extent of complementarity (geometric and/or energy) at the surface of contact is assessed at each position, and the best fits are retrieved. In view of the higher occurrence of hydrophobic groups at contact sites, their contribution results in more intermolecular atom-atom contacts per unit area for correct matches than for false positive fits. The hydrophobic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
137
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(138 citation statements)
references
References 32 publications
1
137
0
Order By: Relevance
“…nantly hydrophobic residues and constitutes a site for interaction with the P domains, whereas the corresponding residues on the surface of the globular subtilisin molecule are hydrophilic. Indeed, analysis of protein-protein interfaces distinguishes the significant contribution of steric contacts between hydrophobic amino acid residues (46)(47)(48). Moreover, surface hydrophobicity can be used to identify regions of a protein surface most likely to interact with a binding ligand (47).…”
Section: The Catalytic and P Domains Interact Through Hydrophobic Patmentioning
confidence: 99%
“…nantly hydrophobic residues and constitutes a site for interaction with the P domains, whereas the corresponding residues on the surface of the globular subtilisin molecule are hydrophilic. Indeed, analysis of protein-protein interfaces distinguishes the significant contribution of steric contacts between hydrophobic amino acid residues (46)(47)(48). Moreover, surface hydrophobicity can be used to identify regions of a protein surface most likely to interact with a binding ligand (47).…”
Section: The Catalytic and P Domains Interact Through Hydrophobic Patmentioning
confidence: 99%
“…Comparisons of the partitioning in the presence of a nonpolar group with that in the presence of the same group carrying a charge (e& COO-or NH3+), or a polar group ( e g , OH), or an unsaturated moiety, has allowed characterization of the binding site (Shanbhag, 1994). Theoretical calculations have shown that a high degree of complementarity between hydrophobic groups and the presence of hydrophobic patches on the surfaces of proteins is correlated with protein binding sites (Korn & Burnett, 1991;Vakser & Aflalo, 1994;Young et al, 1994). These indicate a higher density of hydrophobic atoms at protein-protein interfaces compared with the expected based on overall surface atoms.…”
mentioning
confidence: 99%
“…Volumes of assigned NOESY cross-peaks were converted into 668 proton-proton upper distance limits by the program CALIBA (20) Protein-docking simulations were done with the program GRAMM (v. 1.03) (24) using a standard hydrophobic docking protocol (25). This program employs a geometric recognition algorithm performing an exhaustive six-dimensional search through relative translations and rotations of two molecules in order to provide maximal surface complementarity.…”
mentioning
confidence: 99%